REVITALISASI NILAI-NILAI USHULUDDIN DALAM PROGRAM PENGABDIAN MASYARAKAT - Fauzi, Muhammad Fauzi Noor; Fathimatuz Zahra (LPPM STAI Muhammadiyah Probolinggo, 2025)
This article explores the revitalization of Ushuluddin values within the framework of community engagement programs, particularly through the local traditions of Babalian and Aruh Adat of the Dayak Paramasan community in South Kalimantan. The study aims to demonstrate how the theological, ethical, and humanistic principles of Ushuluddin can be harmoniously integrated into the cultural practices of indigenous societies. Using a descriptive qualitative approach and community-based action research, the findings reveal that these traditions not only embody profound spiritual and social values but also serve as effective media for cultural da'wah. The integration of Ushuluddin values into local customs does not negate indigenous wisdom but rather enriches and strengthens the community’s connection to transcendent values. This Ushuluddin-based community engagement effectively fosters spirituality, preserves social harmony, and reinforces cultural identity amid the challenges of modernization and globalization.